Investment in Climate Smart Livestock by German government - CGIAR Research Program on Climate Change, Agriculture and Food Security; CGIAR Research Program on Livestock (2018)
CCAFS funded ILRI research on improving emissions factors for East African livestock systems in part, enabled ILRI to work with BMZ and GIZ to develop a four year, 11 million Euro project to be implemented with the World Bank in Uganda, Kenya and Ethiopia. The project is the first climate change and livestock project to be funded by the German government. BMZ is following our progress closely.